PROFESSIONALISM AND CARE: THE DAILY BREAD AND BUTTER OF A PARAMEDIC ATTENDING PATIENTS WHO FALL. Issue 5 (18th April 2015) - Simmonds, Bethany; Clarke, Shane; Bradley, Rachel; Benger, Jonathan; Gooberman-Hill, Rachael
Abstract : Falls occur increasingly frequently with age. 35% of people aged over 65 fall each year rising to 50% at age 85. Many patients fall repeatedly. 56% of patients attending an emergency department were recurrent fallers, and 55% of patients presenting with an acute fracture had previously fallen. Fracturing bones is closely linked to falling and carries great costs both for the NHS and the individual. Paramedics do not routinely assess bone health (fracture risk) in people who fall. This is why a study called 'The OAK Project' is being carried out the South West of England to see if it is feasible for paramedics to collect FRAX (The Fracture Risk Assessment Tool) data and whether GPs will put patients with a high risk of fracture on osteoporosis treatment. A significant element of this feasibility study is a qualitative nested study exploring the acceptability of using FRAX amongst patients and paramedics. When shadowing paramedics (n=6), the level of professionalism and care paramedics gave to patients who fell was striking. Paramedics made clinical assessments, gave personal care, emotional support and provided patients with a high level of dignity. When questioned about frequent fallers in interviews (n=12), paramedics felt that in many cases everything possible was being done. GPs are quite often aware of their frequent falling patients, home adaptations had been made, often are already taking medications for osteoporosis, they have personal alarms, home carers who visited frequently and fall assessments had been carried out. Additionally, paramedics felt that some patients do not want to be helped and felt there is a limit to what can be done to prevent people from falling in their own homes. This presentation will provide an insight into the levels of care and professionalism that paramedics demonstrate when attending people who fall in everyday practice.